2023
DOI: 10.7554/elife.82069
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the evolutionary dynamics of predominant SARS-CoV-2 virus lineages co-circulating in Mexico

Abstract: Over 200 different SARS-CoV-2 lineages have been observed in Mexico by November 2021. To investigate lineage replacement dynamics, we applied a phylodynamic approach and explored the evolutionary trajectories of five dominant lineages that circulated during the first year of local transmission. For most lineages, peaks in sampling frequencies coincided with different epidemiological waves of infection in Mexico. Lineages B.1.1.222 and B.1.1.519 exhibited similar dynamics, constituting clades that likely origin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This contrasts with a scenario of worldwide mobility restrictions with fewer successful introductions, resulting in viruses spreading mostly through continuous chains of transmission within Mexico as well as locally acquired mutations that cause geographical clustering. For instance, it has been reported that seven introductions resulted in transmission chains for the Alpha variant, whereas Gamma and Delta had two and six, respectively [ 42 ]. Although the methodology employed in the present study differs and is focused on each subvariant’s early introduction events, this work identified 10 to 17 Mexican clades in these early trees.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with a scenario of worldwide mobility restrictions with fewer successful introductions, resulting in viruses spreading mostly through continuous chains of transmission within Mexico as well as locally acquired mutations that cause geographical clustering. For instance, it has been reported that seven introductions resulted in transmission chains for the Alpha variant, whereas Gamma and Delta had two and six, respectively [ 42 ]. Although the methodology employed in the present study differs and is focused on each subvariant’s early introduction events, this work identified 10 to 17 Mexican clades in these early trees.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because MPXV experienced a stochastic evolutionary event, that led to further diversification of MPXV and contributed to its spread different geographic locations and its possible adaptation to new hosts within these regions 27 Our results reveled that the ancestors of the branches containing Mexican isolates could be traced to the United Kingdom, Portugal, and Canada. This suggests that the sequenced MPXV genomes in Mexico originated from these countries, possibly through travel-associated transmission, as has been observed for other viruses such as SARS-CoV-2, where multiple introductions occur, and only a few viruses manage to establish local transmission chains throughout the country 28,29 .…”
Section: Discussionmentioning
confidence: 76%
“…Secondly, although we have focused on the VOC/VOI that emerged in the LAC, the exclusion of countries from North America and Europe might preclude the identification of transition events between such countries and the LAC. For example, USA and Mexico were shown to have a related Gamma epidemic, with genomes clustering together, especially for the P.1.17 Gamma sublineage 46 . However, the exclusion of countries from Europe and North America probably did not have a great impact on the inferred spread patterns of Lambda and Mu due to the very low prevalence of those variants outside South America.…”
Section: Discussionmentioning
confidence: 99%